The STM analysis of a silver mirror surface - Nikolić Nebojša D.; Rakočević Zlatko; Popov Konstantin I. (Journal of the Serbian Chemical Society, 2001)
In this work, the structure of a silver mirror surface was examined by the STM technique. It was shown that the structural characteristics which enable a high degree of mirror reflection from this surface, which is very close to the ideal reflectivity of silver, are: flat and mutually parallel parts of the surface which are smooth on the atomic level, and distances between adjacent flat parts which state several atomic diameters.